Rainbow trout integrated response after recovery from short-term acute hypoxia - García-Meilán, Irene; Tort, Lluis; Khansari, Ali Reza (Frontiers in Physiology, 2022)
Overcoming a stress situation, such as hypoxia episodes, which involve an allostatic load, will depend on the ability of fish to modulate physiological and biochemical systems to maintain homeostasis. The aim of the study was to determine the integrated stress response after acute hypoxia of the rainbow trout considering the different elements and areas of the stress response: systemic and mucosal, local and global, and from the systemic hypothalamic–pituitary–interrenal axis to skin mucosa. For this purpose, trout were subjected to acute hypoxia (dissolved O2 down to 2 mg/L) for 1 h and then recovered and sampled at 1, 6, and 24 h after reoxygenation. Physiological responses were significantly affected by hypoxic stress and their interaction with time after the challenge, being significant for plasma lactate and cortisol levels, in both plasma and skin mucus. At the central brain level, only trh expression was modulated 1 h after hypoxia which indicates that brain function is not heavily affected by this particular stress. Unlike the brain, the head kidney and skin were more affected by hypoxia and reoxygenation. In the head kidney, an upregulation in the expression of most of the genes studied (gr, il1β, il6, tgfβ1, lysozyme, caspase 3, enolase, hif-1, myoglobin, sod2, gpx, gst, and gsr) took place 6 h after recovery, whereas only hsp70 and il10 were upregulated after 1 h. On the contrary, in the skin, most of the analyzed genes showed a higher upregulation during 1 h after stress suggesting that, in the skin, a local response took place as soon as the stressor was detected, thus indicating the importance of the skin in the building of a stress response, whereas the interrenal tissue participated in a later time point to help prevent further alteration at the central level. The present results also show that, even though the stressor is a physical/environmental stressor, all components of the biological systems participate in the regulation of the response process and the recovery process, including neuroendocrine, metabolism, and immunity.